Some Rigidity Theorems of Closed Geodesic Polygons and Spherical Curves in Metric Spaces with Curvature Bounded Below (European Journal of Pure and Applied Mathematics, 2024)
This paper examines characterizations of closed curves in a geodesic metric space with curvature bounded below, including closed geodesic polygons and closed spherical curves bounding surfaces isometric to convex polygons and circles in the model space.
Keywords: spaces with curvature bounded below; convex hull; closed geodesic polygon; spherical curve; isometry